Longitudinal uniformity of MgB2 wires made by an internal magnesium diffusion process. (20th August 2021) - Kováč, P; Hušek, I; Hain, M; Kopera, L; Melišek, T; Berek, D
Abstract: Single- and multi-core MgB2 wires have been fabricated by an internal Mg diffusion (IMD) process. Wires uniformity after drawing and/or rolling deformation has been studied by optical microscopy and x-ray micro-tomography. Several short samples taken lengthwise between both ends of the wire were annealed and their critical current measured. It was found that I c of the single-core barrier-free MgB2 /Fe wire with high fill factor (32.5% of MgB2 ) vary by 100% towards the averaged I c . Multi-core wire having ∼15.0% of MgB2 and Cu outer sheath shows better uniformity with 25% deviation of I c over the 10 m length, which is still quite low and needs some improvements. It is expected, that improved in-length uniformity can be reached only for filamentary IMD wires with optimized deforming process and mechanically stronger outer sheath.